2021
DOI: 10.1111/ijcp.14120
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilisation pattern over 3 years in the real‐world treatment of type II diabetes

Abstract: Introduction Non‐adherence to therapy is very common in patients with type II diabetes, leading to an increase in morbidity and mortality. The development of new oral therapies following metformin has increased the possibilities of treatment but little has been done in terms of improving medication adherence. The goal of the following study is to evaluate adherence and persistence over a period of 3 years in real‐world diabetic patients and describe the comorbidities found in the group of patients studied. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, [28][29][30][32][33][34][35][36][37][38] highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration. Interestingly, we observed that SMBG was independently associated with hypoglycemia in both study populations.…”
Section: Ta B L E 2 Association Between Smbg and Hba1c < 7%supporting
confidence: 90%
“…Patients with diabetes mellitus (DM) present with abnormal blood glucose and long-term organ damage, leading to cardiovascular diseases and increasing the disease-associated burden [1][2][3]. Therefore, early diagnosis and treatment should be carried out to strictly control the occurrence of DM.…”
Section: Introductionmentioning
confidence: 99%
“…The second‐line OADs investigated in these studies were the DPP4i alogliptin and the SGLT2is canagliflozin, dapagliflozin, and empagliflozin. Furthermore, Gordon et al., 21 Romagnoli et al., 22 and Strain et al. 23 investigated adherence to SGLT2is, but did not report the type of SGLT2is being investigated.…”
Section: Resultsmentioning
confidence: 99%